PENGARUH VARIASI SUHU DAN WAKTU EKSTRAKSI ULTRASONIK TERHADAP AKTIVITAS ANTIBAKTERI EKSTRAK RUMPUT LAUT (Gracilaria gracilis) PADA BAKTERI Staphlococcus aureus - Awang Pratama Susilo Putra (2023)
Seaweed (Gracilaria gracilis) is known to have many benefits, one of which is that it is a natural antibacterial agent. The temperature and time used during the extraction process will determine the quality of the extract. This study aims to determine the effect of temperature and ultrasonic extraction time on the antibacterial activity of Gracilaria gracilis extract using the disc diffusion method. The ultrasonic extraction method was carried out using variations in temperature (50°C, 60 °C, and 70°C) and time (15, 25, and 35 minutes). The extract with the highest flavonoid content at each temperature will be tested for its antibacterial activity on Staphylococcus aureus bacteria. The results showed that the extraction group at 50°C for 35 minutes had the highest value of flavonoid content, which was 7.99 mg QE/g and resulted in an inhibition zone diameter of 13.81 mm. Ultrasonic extraction temperature and time had a significant effect on the antibacterial activity of Gracilaria gracilis extract, with a significance value of p = 0 (p ≤ 0.05).